Maxillary unilateral parastyle: An Orthodontist's Conundrum - Abirami Ramesh; Priyanka Madhavan; Vivek Amin; Jaya Ramesh (Journal of Dental Problems and Solutions - Peertechz Publications, 2021)
The developmental anomalies can be in the form of mild alteration in shape of crown or root such as development of an extra supernumerary cusp in both primary and permanent dentition. Such developmental disturbances are rare in permanent dentition. Parastyle is one common form of accessory cusp of permanent mandibular molar. Though its presence is not an alarming condition, it is of great importance in medicolegal cases. We herein report a case of parastyle on permanent maxillary second molar, its development, classification, histopathological appearance and its clinical implications.